The effect of quality culture on service quality; infrastructure quality as a mediation variable - Kartini, Kartini; Samdin, Samdin; Ramli, Ramli; Sinarwati, Sinarwati; Zaludin, Zaludin (International Journal of Applied Economics, Finance and Accounting, 2023)
This study aims to examine the influence of quality culture on service quality, the influence of quality culture on infrastructure quality, the influence of infrastructure quality on service quality, the role of infrastructure quality in mediating the influence of quality culture on service quality mediated by infrastructure quality. The population of this study are 176 pupils from class IX, or junior high school, at Umusshabri Kendari Educational Institution. The study sample was determined to be 176 after it was calculated using a technical census. employing questionnaires to acquire data. The research model is structural; thus, the data analysis uses Smart Partial Least Square PLS version3 software to examine direct influences and indirect influences. The findings of this study show the quality culture has a positive and significant effect on service quality, quality culture has a positive and significant effect on infrastructure quality, infrastructure quality has a positive and significant effect on service quality, infrastructure quality plays a role in partially mediating the influence of quality culture on service quality. Based on these findings, it is crucial for educational institutions to establish a culture of quality in order to enhance the quality of the infrastructure and the services provided to students in order to help them develop as people and provide them the skills they need to live better.